The impact of demographic dynamics on economic development, poverty and inequality in Mozambique - Stephan Klasen; Silke Woltermann (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2005)
In this paper, we analyze whether current demographic dynamics in Mozambique are likely to reduce per capita growth and poverty reduction. The findings suggest that population dynamics do not appear to be a major driver of changes in growth of per capita incomes, poverty, or inequality. At the macro level this can be seen at the off-setting effects of population growth on the one hand and the potential to reap the benefits of a demographic giftand higher population density on the other. At the micro level, it is clear that household size has not changed drastically and the existing negative impact of household size on poverty and inequality appears to have fallen in recent years, particularly in rural areas. Thus demographic dynamics have helped support rising per capita incomes and falling poverty rather than hindering it.
Keywords: J1; I32; O15; 330; poverty; inequality; population growth; Mozambique; Bevölkerungsentwicklung; Entwicklung; Armut; Einkommensverteilung; Mosambik; Uganda